Selection of young basketball players: A study with brazilian coaches - Valmor Ramos; Fernando José da Silva Tavares (Universidade Federal de Santa Catarina, 2000)
The purpose of this research was to analyze the criteria employed by Brazilian basketball coaches to select young basketball players. This a descriptive research study with a sample comprising 16 basketball coaches (8 female and 8 male). All were training teams participating in the IV Youth Games - Division A. Data collection was by questionnaire and attitude scales, including topics such as indicators and methodology for selecting young basketball players. Based on the results the main conclusions were: 1) Brazilian coaches have a clear definition of the indicators for selecting young basketball players for specific positions; 2) Coaches have a process for the selection of young basketball players; 3) Selection is based predominantly on the coach's knowledge and experience. RESUMO O objetivo desta pesquisa foi de analisar o processo de seleção de jovens atletas de basquetebol, realizado pelos técnicos brasileiros de basquetebol. Este estudo caracteriza-se por uma pesquisa de campo de natureza descritiva, sendo a amostra constituída de 16 indivíduos (8 técnicos das equipes masculinas e 8 técnicos das equipes femininas). Todos das equipes representativas dos estados do Brasil no IV Jogos da Juventude - divisão "A". Para a coleta de dados utilizou-se um questionário com questões fechadas e escalas de atitude, onde são abordados temas como: Indicadores de seleção considerados no processo de seleção de jovens atletas de basquetebol; e Procedimentos metodológicos de seleção desportiva. Da análise dos resultados obtidos emergem as principais conclusões: 1) Os técnicos brasileiros possuem conhecimento definido dos indicadores que devem ser considerados na seleção dos jovens atletas para cada posto específico; 2) Eles apresentam um processo definido para a seleção de jovens atletas de basquetebol 3) O processo de seleção está centrado preponderantemente no conhecimento e experiência do técnico.